Pharmacokinetics of methotrexate in rabbits and six neoplastic patients - LONG Qi-cai; PAN Qi-chao (Acta Pharmacologica Sinica, 2016)
Plasma concentrations of methotrexate in 6 cancer patients and 5 rabbits after iv were determined by microbiological method (filter paper disc on plate). The concentrationtime curves were shown to be of first linear kinetic pattern, three-comparment for patiens and two-compartment for rabbits. Plasma concentration of methotrexate capable to inhibit DNA biosynthesis lasted 12 h in all patients. In 5/6 patients, the plasma methotrexate concentrations that were higher than the toxic threshold did not reach 42 h (toxic threshold time). The excretion rate of methotrexate in rabbits was rather fast.